Understanding the financial literacy of undergraduate students at Thai universities - Angsana Channak (2022)
This paper explores the financial literacy of undergraduate students at Thai universities. Four hundred questionnaires were distributed to undergraduate students based on systematic random sampling and the results were analyzed by descriptive statistics. The participants knew about simple interest, basic savings, investment risk, and inflation but were confused about compound interest. Most had no savings and had faced financial problems during the last 6–12 months. They were also happier with spending than saving. Owing to such financial illiteracy, educational courses that include financial concepts and skills must be offered to improve students’ financial attitude and behavior.